Increases in pharyngeal Neisseria gonorrhoeae positivity in men who have sex with men, 2011–2015: observational study. (17th October 2019) - Comninos, Nicholas Byron; Garton, Linda; Guy, Rebecca; Callander, Denton; Fairley, Christopher K; Grulich, Andrew E; Donovan, Basil; Goddard, Sian Louise; Rutherford, Alison; Templeton, David J
Abstract : Objectives: Pharyngeal gonorrhoea disproportionately affects men who have sex with men (MSM). We explored temporal trends in pharyngeal gonorrhoea positivity among MSM compared with anorectal and urogenital positivity. Methods: Data (2011–2015) were extracted from 41 publicly funded sexual health clinics participating in a national surveillance network. Positivity was defined as the proportion of first-visit testing occasions where gonorrhoea was detected. Logistic regression explored trends in positivity and correlates of positive pharyngeal tests. Results: From 2011 to 2015, 24 792 MSM tested (16 710 pharyngeal, 19 810 urogenital and 15 974 anorectal first-visit tests). Pharyngeal positivity increased by 183% from 139/3509 (4.0%) in 2011 to 397/3509 (11.3%) in 2015, p-trend <0.001; urogenital positivity by 39% from 257/4615 (5.6%) to 295/3783 (7.8%), p-trend=0.006; and anorectal positivity by 87% from 160/3469 (4.6%) to 286/3334 (8.6%), p-trend <0.001. The annual temporal increase in positivity was greater in the pharynx (OR 1.33; 95% CI 1.27 to 1.38) than at urogenital (OR 1.06; 95% CI 1.02 to 1.10) and anorectal (OR 1.16; 95% CI 1.11 to 1.21) sites. Factors independently associated with pharyngeal gonorrhoea were: younger age (p<0.001), higher numbers of recent sexual partners (p-trend=0.004), contact with a person with a diagnosed STI (p<0.001), injecting drug use (p<0.001), anogenital symptoms (p<0.001) and HIV-positive status (p=0.050). Conclusion: Temporal increases in gonorrhoea positivity occurred at all anatomical sites, with the greatest increase in the pharynx. Risk factors could be used to help to develop testing and prevention strategies among MSM at highest risk. Strengthening sexual health service delivery, testing and surveillance remain priorities for pharyngeal gonorrhoea control.